War, massacre, and recovery in Central Italy, 1943-1948 - Belco, Victoria, 1952- (Toronto Italian studies., 2010)
"The Second World War wreaked unprecedented devastation throughout Europe, necessitating monumental reconstruction efforts that burdened not only governments, but the lives of ordinary citizens. War, Massacre, and Recovery in Central Italy, 1943-1948 examines this transitional period in the province of Arezzo by detailing the daily experiences of civilians through the traumas of war and the difficulties of recovery.